Chatbots and Voicebots on E-Learning Platforms to Promote Job-Related Conversational Skills in Daf / Daz Lessons - Szerszeń, Paweł; Wolski, Przemysław (Germanistinnen und Germanisten im Beruf – zwischen Ausbildung und Realität, 2020)
The study addresses the question of the extent to which interactive communication systems can contribute to the promotion of job-related conversational competence, which is intended by their implementation in already functioning learning platforms. Interactive communication systems are understood here as so-called “talking chatbots” or “voicebots”, which function by analyzing the user input and generating communicationadequate answers using natural language processing (NLP) and artificial intelligence. They usually consist of three parts: a database (the knowledge base) which provides a framework for the “intelligence” of the system, a software engine which controls the interface and the interpreter which communicates with the interface through its analyzer and generator. In the case of a talking chatbot, the interface is equipped with a speech recognition software and speech synthesis software. In the case of a chatbot, which complements an e-learning platform for the promotion of job-related linguisticcommunicative competence, the database consists of entries originating from the corpora of the spoken language or collected through procedures of language needs assessment. The article first attempts to critically assess the latest developments in the field of e-learning supported vocational DaF/DaZ teaching. The second part of the article focuses on elements of subjective theories of students that were collected in a standardized survey. The opinions concerning the use of interactive systems in university German as a foreign language courses will be examined in the context of selected psychological dispositions such as control conviction, Machiavellianism or acceptance of constructivist didactics. Based on this, it is discussed how the process of task design could look like in such learning environments. On the basis of connectivist learning theories, an attempt is also made to propose a model of digitally supported task solving in the field of blended learning.